Two-dimensional diagonal layer hash chain based key pre-distribution scheme. (December 2021) - Yang, Ching-Nung; Kao, Chung-Lun; Wang, Chang-Ji
Highlights: Enhnacing the resilience of node-capture attack when compared with previous hash chain based key pre-distribution scheme. The proposed scheme can resist the advanced node-capture attack, while previous schemes cannot. Theoretical analyses are given to demonstrate our better performance. Abstract: Recently, Ehdaie et al. proposed a two-dimensional hash chain based key pre-distribution (2DHC-KPD) scheme that can enhance resiliency against node-capture attack when compared with the conventional hash chain based key pre-distribution (HC-KPD) scheme. However, these HC-KPD-like schemes cannot resist the advanced node-capture attack (ANA) that attackers have the knowledge of the identifiers of sensor nodes. In this paper, we adopt the diagonal layer from the two-dimensional key map in 2DHC-KPD scheme to design the diagonal layer hash chain based key pre-distribution (DLHC-KPD) scheme. Compared with all HC-KPD-like schemes, our DLHC-KPD scheme has the best resiliency against node-capture attack, and is also the only scheme that can resist against the ANA. The trade-off is more hash operations.